Is triple-positive serology for Epstein-Barr virus (VCA-IgG, VCA-IgM, EBNA-IgG) a specific feature of angioimmunoblastic T-cell lymphoma?. Issue 5 (October 2020) - Facchinelli, Davide; Parisi, Alice; Krampera, Mauro; Veneri, Dino
Purpose: We assessed the frequency of triple-positive serology (viral capsid antigen [VCA]–immunoglobulin G [IgG], VCA–immunoglobulin M, Epstein-Barr nuclear antigen–IgG) for Epstein-Barr virus (EBV) in a small number of patients with angioimmunoblastic T-cell lymphoma (AITL) at disease onset. Methods: Nine patients with newly diagnosed AITL were retrospectively enrolled in the present study. For all of them, EBV serology data were available. Results: Of 9 patients, 7 (77.7%) had a triple-positive serology (VCA-IgG, VCA-IgM, EBNA-IgG ) for EBV. These patients were characterized by bone marrow involvement, high incidence of thrombocytopenia, and poor prognosis according to Revised International Prognostic Index and Prognostic Index for Angioimmunoblastic T-cell Lymphoma scores. Conclusion: Assessment of both viremia and serology for EBV could be useful in patients with clinical and laboratory data suggesting lymphoma diagnosis; furthermore, although our data need to be validated in a larger cohort of patients, triple positivity for EBV serology might help to direct the diagnosis toward AITL.